Arduino Cookbook, 3rd Edition - Margolis, Michael; Jepson, Brian (O'Reilly Media, Inc., 2020)
Want to create devices that interact with the physical world? This cookbook is perfect for anyone who wants to experiment with the popular Arduino microcontroller and programming environment. You'll find more than 200 tips and techniques for building a variety of objects and prototypes such as IoT solutions, environmental monitors, location and position-aware systems, and products that can respond to touch, sound, heat, and light. You don't need to have mastered Arduino or programming to get started. Updated for the Arduino 1.5 release, the recipes in this third edition include practical examples and guidance to help you begin, expand, and enhance your projects right away-whether you're an engineer, designer, artist, student, or hobbyist. Get up to speed on the Arduino board and essential software concepts quickly Learn basic techniques for reading digital and analog signals Use Arduino with a variety of popular input devices and sensors Drive visual displays, generate sound, and control several types of motors Interact with devices that use remote controls, including TVs and appliances Learn techniques for handling time delays and time measurement Apply advanced coding and memory-handling techniques.
Online resource; Title from title page (viewed April 25, 2020)